A nationwide blood spot screening study for Fabry disease in the Czech Republic haemodialysis patient population - Merta, Miroslav; Reiterova, Jana; Ledvinova, Jana; Poupetová, Helena; Dobrovolny, Robert; Rysavá, Romana; Maixnerová, Dita; Bultas, Jan; Motán, Jirí; Slivkova, Jitka; Sobotova, Doris; Smrzova, Jana; et al. (Nephrology, dialysis, transplantation, 2007)
BACKGROUND: Fabry disease (FD) is a genetic disorder characterized by accumulation of trihexosylceramide in lysosomes of various tissues leading to multiorgan manifestations, including progressive renal disease. Previous screening studies have shown that a non-neglectable proportion of haemodialysis(HD) patients have unsuspected FD. An extensive FD screening study, the largest to date, has been conducted in HD patients in Czech Republic. We aimed to uncover previously undiagnosed FD patients, to enable them to benefit from cause-specific therapeutic intervention with enzyme replacement therapy (ERT). METHODS: Large-scale screening was executed using a convenient automated enzymatic (alpha-galactosidose A, alpha-Gal A) dried blood spot on filter paper fluorescence method. RESULTS: In total, 3370 (45.1% males, 54.9% females) out of 4058 HD patients (83%) in Czech Republic participated in this blood spot screening (BSS) study. Abnormal low fluorescence readings were obtained in 117 patients (3.5%). Subsequent determination of plasma alpha-Gal A activity identified four males and three females with deficient plasma enzyme activity. Determination of alpha-Gal A activity in peripheral blood leucocytes and confirmatory molecular analysis resulted in four newly diagnosed Fabry males and one female. Subsequent family screening identified 10 family members with genotypically proven FD. Based on these screening results, ERT could be offered to five male FD patients. CONCLUSIONS: BSS represents a promising screening tool that has proven to be convenient and effective in uncovering unrecognized FD patients among the chronic HD population in Czech Republic.
Keywords: Fabry Disease; Male; Pedigree; alpha-Galactosidase; rodokmen; fluorescenční spektrometrie; Lysosomes; Česká republika; Fabryho nemoc; dialýza ledvin; Adult; Aged; dospělí; mužské pohlaví; senioři; lyzozomy; Czech Republic; Renal Dialysis; lidé; ženské pohlaví; konformace proteinů; Humans; enzymoterapie; Protein Conformation; Enzyme Therapy; Spectrometry, Fluorescence; alfa-galaktosidasa; Female; lidé středního věku; Middle Aged